THE EFFECTIVENESS OF THE ROLE OF COMMUNITY GUIDANCE IN CONDITIONAL RELEASE AT PRABUMULIH CORRECTIONAL CENTER - Lusi Hertina; Abdul Latif Mahfuz; Syamsul Syamsul (Universitas Nusa Cendana, 2026)
This study analyzes the effectiveness of Community Counselors in implementing conditional release at the Prabumulih Community Guidance Center (Pos Balai Pemasyarakatan Class IIB), with a focus on factors influencing the reintegration of clients into society. Using an empirical legal approach with a sociological perspective, the research employs qualitative methods, including interviews, observations, and document analysis involving counselors, clients, and related officials. The findings show that Community Counselors play a crucial role in supervising, guiding, and supporting individuals undergoing conditional release. They act as facilitators of reintegration by providing direction, monitoring behavior, and assisting clients in adapting to social life. However, the effectiveness of their role is constrained by several challenges. These include limited human resources, high counselor-to-client ratios, inadequate infrastructure, and persistent social stigma toward former inmates. These conditions reduce the ability of counselors to provide personalized guidance and optimal supervision, which in turn affects the success of the reintegration process. In conclusion, strengthening the role of Community Counselors is essential to improving conditional release outcomes. This can be achieved by increasing the number of counselors, enhancing institutional resources, improving coordination between agencies, and addressing societal stigma to support successful reintegration and reduce recidivism. Keywords: Conditional Release; Community Counselors; Social Reintegration